Synthesis of 2-Arylimino Thiazol [4,5-e] (1,4) Diazepines - Rajput, A.P. (Asian Journal of Chemistry, 2010)
Benzodiazepines possess a variety of useful biological activities, pharmaceutical properties and therapeutic applications. Their discovery has opened a new era in the research of drugs acting on the central nervous system. Their clinical importance and commercial success tempted us to synthesize 1,4-diazepine type compounds.